Proceedings of 4th Nordic Conference on Construction Economics and Organisation : Development Processes in Construction Management. 14th-15th June 2007 - Atkin, Brian; Borgbrant, Jan (Luleå, 2007)
The conference was organised by the Swedish national research and development programme for construction, Competitive Building, and the Construction Management Research Group, Department of Civil and Environmental Engineering, Luleå University of Technology, Luleå, Sweden. Godkänd; 2007; 20071220 (ysko)